Microplastic Analysis in Mackarel Tuna and Milkfish at Selili Fish Landing Site, East Kalimantan - Mahesa Islamy Eka Juniar; Abdunnur; Moh Mustakim; Irwan Suyatna; Fitriyana (Grouper, 2025)
Microplastic pollution in coastal waters poses a serious threat to marine ecosystem sustainability and food safety. However, data on microplastic contamination in edible fish from the Selili Fish Landing Station (PPI Selili), Samarinda, remains limited. This study aimed to identify the types and abundance of microplastics in mackarel tuna (Euthynnus affinis) and milkfish (Chanos chanos), and to analyze the relationship between fish size and microplastic count. The methodology involved random sampling, microplastic extraction from digestive tracts using 22% KOH solution, and statistical analysis using ANOVA and linear regression. The results showed that mackarel tuna contained an average of 3.87 particles per individual, while milkfish had 1.8 particles per individual. The dominant type of microplastic in both species was film (>80%). ANOVA revealed a significant difference in microplastic abundance between the two species (p = 0.010), whereas regression analysis indicated that fish length and weight had no significant effect on microplastic quantity (R² < 0.03). In conclusion, mackarel tuna are more prone to microplastic accumulation than milkfish, likely due to differences in habitat and feeding behavior. It is recommended to conduct regular monitoring of water quality and educate local communities about reducing single-use plastic to minimize microplastic pollution around PPI Selili.